Electroporation Therapy in Soft Tissue Sarcoma: A Potentially Effective Novel Treatment - de Bree, Remco (Hindawi Publishing Corporation, 2006)
Purpose. Examination of the potential of electroporation therapy (EPT) in a patient with metastatic soft tissue sarcoma. Patient. A 24-year-old male who underwent extensive resection and postoperative radiotherapy for a malignant peripheral nerve sheath tumor in the right infratemporal fossa with intracranial extension and invasion of the maxillary sinus and mandible had a recurrence in the scar of his craniotomy for which he was initially treated with doxorubicin. After discontinuation of doxorubicin he developed a metastatic mass at the same site for which he was treated with electroporation therapy. Method. The subcutaneous metastasis was infiltrated with bleomycin and electroporated. Results. Gradually the tumor became increasingly necrotic and demarcated from surrounding tissue. After 10 weeks no tumor was seen anymore. The wound healed secondarily. Discussion. Intralesional bleomycin followed by EPT is potentially effective, well tolerated, and easy to perform in well accessible soft tissue sarcoma sites.